Comparative evaluation of several methods for Canine Visceral Leishmaniasis diagnosis - Silva, Diogo Tiago da [UNESP]; Starke-Buzetti, Wilma Aparecida [UNESP]; Alves-Martin, Maria Fernanda [UNESP]; Paixão, Mirian dos Santos [UNESP]; Tenório, Michely da Silva [UNESP]; Martins Lopes, Mara Lúcia [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
The aim of the present study was to evaluate the serological methods using ELISA with recombinant-rK39 (ELISA-rK-39) and soluble extract-SE (ELISA-SE) antigens, the indirect fluorescence antibody test (IFAT) in comparison to an immunochromatography rapid diagnostic test (RDT-rK39) and with a direct parasitological exam (PA) for Canine Visceral Leishmaniasis (CVL) diagnosis. The results showed that 89% (60/67) of the dogs were positive for at least one serological diagnostic test. ELISA-SE was the test that detected anti-Leishmania antibodies in the serum of the highest number of dogs (71.6%) followed by ELISA-rK39 (65.7%), IFAT (65.7%) and RDT-rK39 (55.2%). PA detected the lowest numbers (40.3%) of positive dogs. In relation to the total of examined dogs, the Kappa indexes (p=0.05) showed a good agreement between ELISA-SE and IFAT (88.1%; k=0.7237), and it was also observed in the comparison of RDT-rK39 with ELISA-SE (83.6%, k=0.6561), IFAT (83.5%, k=0.6605) and PA (85.0%, k=0.7074). A bad agreement was detected in any association of ELISA-rk39 with the other tests in either symptomatic or asymptomatic animals. ELISA as well as RDT using recombinant antigenic protein (rK39) were the methods that detected the lowest prevalence rates (33.3%) of CVL in asymptomatic dogs. In conclusion, only one test does not adequately identify dogs with CVL and it is necessary the association of two or more diagnostic tests. Because of the good agreement indexes of RDT-rK39 when evaluated with ELISA-SE, IFAT and PA it was suggested as a complementary method to be used in association with either ELISA-SE or IFAT, particularly in the symptomatic dogs. Furthermore, new studies are recommended in order to improve the sensitivity of tests mainly for asymptomatic dogs.

O objetivo do presente estudo foi avaliar os métodos sorológicos usando ELISA (Ensaio Imunoenzimático Indireto) com o antígeno recombinante rK39 (ELISA-rK39) e o antígeno extrato solúvel bruto (ELISA-ES) e a RIFI (Reação de Imunofluorescência Indireta) em comparação com o método imunocromatográfico rápido (RDT-rK39) e o parasitológico direto (PA), para o diagnóstico da Leishmaniose Visceral Canina (LVC) em cães de Ilha Solteira, São Paulo, Brasil. Os resultados mostraram que 89% (60/67) dos cães foram positivos por pelo menos um teste diagnóstico sorológico (RIFI, ELISA-ES, ELISA-rk39 ou RDT-rK39) e somente 40,3% (27/67) foram positivos pelo PA. O ELISA-ES foi o teste que detectou anticorpos anti-Leishmania em maior número de cães (71,6%) seguido por ELISA-rK39, RIFI (65,7%) e por RDT-rK39 (55,2%). No total de cães analisados (assintomáticos e sintomáticos), o índice Kappa de concordância (p ≤ 0,05) foi considerado de boa concordância entre ELISA-ES e IFAT (88,1%; k= 0,7237) e entre RDT-rK39 com ELISA-ES (83,6%, k= 0,6561), RIFI (83,5%, k= 0,6605) e PA (85,0%, k= 0,7074). O índice de concordância ruim foi observado em qualquer associação de ELISA-rk39 com todos os outros testes nos animais sintomáticos e nos assintomáticos. Tanto o ELISA como o RDT com proteínas recombinantes (rK39) detectaram a menor porcentagem de cães assintomáticos (33,3%) em relação aos outros testes sorológicos. Em conclusão, somente um método diagnóstico não foi suficiente para identificar todos os cães positivos com LVC, principalmente os assintomáticos e por isso foi necessário a associação de dois ou mais métodos. Em função da boa concordância do teste RDT-rK39 com ELISA-ES, RIFI e PA, o mesmo foi sugerido como um teste complementar ao ELISA-ES ou RIFI para o diagnóstico da LVC, principalmente dos cães sintomáticos. No entanto, novos estudos são recomendados para melhorar a sensibilidade dos testes principalmente para cães assintomáticos.
Avaliação comparativa entre vários métodos para o diagnóstico da Leishmaniose Visceral Canina
Keywords: CVL; Diagnosis; Dogs; Leishmania infantum; rK39; RDT; LVC; Diagnóstico cães; Leishmania infantum; rK39; RDT